2010
DOI: 10.1371/journal.pone.0011721
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Incidence and Mortality in Mainland China: Systematic Review of Chinese and English Literature, 1985–2008

Abstract: BackgroundPneumonia is a leading infectious disease killer worldwide, yet the burden in China is not well understood as much of the data is published in the non-English literature.Methodology/Principal FindingsWe systematically reviewed the Chinese- and English-language literature for studies with primary data on pneumonia incidence and mortality in mainland China. Between 1985 and 2008, 37 studies met the inclusion criteria. The quality of the studies was highly variable. For children <5 years, incidence rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 26 publications
1
48
0
3
Order By: Relevance
“…By comparison, the incidence of pneumonia and acute respiratory infections is quite low in developed countries [10]. It is reported that the incidence of childhood pneumonia is only 0.02% to 0.38% episodes per child-year among children <5 years old in Norway, USA, Finland, Scotland and UK [11][12][13][14], while it was reported that to be 6%-27% episodes per childe-year among children <5 years in China [9]. The same conclusions were found by Rudan et al [3] that the incidence estimated to be 0.29 episodes per child-year in developing and 0.05 episodes per child-year in developed countries among children<5 years.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By comparison, the incidence of pneumonia and acute respiratory infections is quite low in developed countries [10]. It is reported that the incidence of childhood pneumonia is only 0.02% to 0.38% episodes per child-year among children <5 years old in Norway, USA, Finland, Scotland and UK [11][12][13][14], while it was reported that to be 6%-27% episodes per childe-year among children <5 years in China [9]. The same conclusions were found by Rudan et al [3] that the incidence estimated to be 0.29 episodes per child-year in developing and 0.05 episodes per child-year in developed countries among children<5 years.…”
mentioning
confidence: 99%
“…Zhang [8] reviewed the literature on childhood pneumonia in China and found that the incidence of pneumonia for children <5 years old was 26.5% (95% CI: 26.3%-26.7%) south of the Yangtze River, and 8.4% (95% CI: 8.2%-8.7%) north of Yangtze River. Zhang [8] and Guan et al [9] found no significant differences in childhood pneumonia incidence between the West and East of China. By comparison, the incidence of pneumonia and acute respiratory infections is quite low in developed countries [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Early diagnosis of severe pneumonia can enable patients to receive immediate medical attention by transferral to the ICU for further treatment, 18 and appropriate early intervention may improve their outcomes. 19 However, blindly depending on clinical presentations, routine examinations, and scoring systems may substantially reduce the accuracy of predicting the outcomes of severe pneumonia in patients, delaying treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 Data for persons 65 years of age and older were taken from a previously published local analysis. 23 …”
Section: Disease Incidence and Case Fatality Ratesmentioning
confidence: 99%